Special Interests and Technological Change - Giorgio Bellettini; Gianmarco I.P. Ottaviano (Fondazione Eni Enrico Mattei (FEEM), 2003)
We study an OLG economy where productivity growth comes from two alternative sources: process innovation and learning-by-doing. There is a trade-off between the two in so far as frequent technological updates reduce the scope for learning on existing technologies. A conflict is shown to arise between the young and the old, because the former favor innovation while the latter prefer learning. We model the interaction between overlapping generations and policy makers as a dynamic common agency problem, where competing generations invest a certain amount of resources to lobby either for the maintenance of the current technology or the adoption of a new one. By focusing on truthful Markov perfect equilibria, we characterize the political equilibrium and show its dependence on the underlying demographic, technological and preference parameters.
Keywords: C72; C73; D72; O38; O41; 330; Technological change; Technology option; Pressure goups; Dynamic common agency; Technischer Fortschritt; Produktivität; Interessenvertretung; Overlapping Generations; Theorie